2015
DOI: 10.1073/pnas.1421845112
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and extracellular forces drive primary cilia movement

Abstract: Primary cilia are ubiquitous, microtubule-based organelles that play diverse roles in sensory transduction in many eukaryotic cells. They interrogate the cellular environment through chemosensing, osmosensing, and mechanosensing using receptors and ion channels in the ciliary membrane. Little is known about the mechanical and structural properties of the cilium and how these properties contribute to ciliary perception. We probed the mechanical responses of primary cilia from kidney epithelial cells [Madin-Darb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 55 publications
4
69
0
Order By: Relevance
“…© Springer-Verlag 1999, with kind permission from Springer Science and Business Media. tween macrophages and apoptotic cells could be demonstrated in the catshark (Bejarano-Escobar et al, 2013). For these and other reasons, Francisco-Morcillo et al (2014) conclude that, in the developing visual system, "dying cells show similar but not identical spatiotemporally restricted patterns in different vertebrates".…”
Section: Cerebellummentioning
confidence: 99%
See 1 more Smart Citation
“…© Springer-Verlag 1999, with kind permission from Springer Science and Business Media. tween macrophages and apoptotic cells could be demonstrated in the catshark (Bejarano-Escobar et al, 2013). For these and other reasons, Francisco-Morcillo et al (2014) conclude that, in the developing visual system, "dying cells show similar but not identical spatiotemporally restricted patterns in different vertebrates".…”
Section: Cerebellummentioning
confidence: 99%
“…However, it is still unclear how this type of planar polarity is established in cones and what its functional impacts are. This may be about to change in view of the exciting new discovery that, in kidney epithelial cells, primary cilia (9 + 0 cilia) undergo active fluctuations in the absence of dyneins (Battle et al, 2015). small supranuclear mitochondria are attached to cytoplasmic microtubules (MT).…”
Section: Ciliogenesis In Photoreceptor Cellsmentioning
confidence: 99%
“…The Hippo pathway both controls and is regulated by the primary cilia [94,153155], a microtubule-based solitary sensory signaling organelle comprising a special part of the plasma membrane in most eukaryotic quiescent cells [156]. The primary cilia respond to mechanical signals [157] and dynamically localize and regulate a range of receptors mediated by YAP/TAZ, such as GPCRs, sonic hedgehog (shh), the TGFβ family, receptor tyrosine kinases, and Wnt receptors [7,10,14,17,22,23,158]. This regulation of receptors is predominantly mediated through the cilia transition zone, the cellular gatekeeper for receptors destined for cilial localization [156].…”
Section: Yap/taz As a Signaling Networkmentioning
confidence: 99%
“…For example, primary cilia are distinct from motile cilia which contain actin filaments to drive motion, and it was believed that primary cilia lacked this actin connectivity. However, APEX labeling uncovered that actin and actin-binding proteins are actually trafficked to the primary cilium as well, potentially supporting the hypothesis that actin forces tune cilia mechanosensing [73]. …”
Section: Vi: Future Directionsmentioning
confidence: 96%
“…It has been suggested that the actin cytoskeleton surrounding the basal body of the cilium may also generate force to adjust ciliary positioning to tune and calibrate sensory functions [73]. In fact, treatment with the actin destabilizer, cytochalasin D, induces ciliogenesis, though it has not been clearly defined how this impacts primary cilia-medaited mechanotransduction [74].…”
Section: Primary Cilia Structure Dictates Mechanosensingmentioning
confidence: 99%